Identitas Lokal Dan Global Dalam Iklan - Murtono, Taufik (Acintya, 2009)
This article incorporate globalization issue in advertising industry in Indonesia, particulary in discussing the presence of dultural identity in global world context. The finding abaout the modus of advertising strategy gives comprehension on how commercial advertisement communicate the identitiy they were offered. Identitiy works in many patterns those used product figure, verbal language and visual symbol. The existence of mixed identity as it appears in global products those try to use local element in their advertising while some local products do the contrary-show that identities srocc reference had happened in advertising world.Keyword : identity, globalization, advertisement